Brand extensions’ influence on brand image : empirical study on Bodrex’sbrand - Rokhman, M. Rifqi; ., Sampurno; S., Suci Paramitasari (Indonesian Journal of Pharmacy, 2010)
Bodrex’s manufacturer is attempting to use Bodrex brand success to enter flu  and  cough  medicine  category  by  releasing  Bodrex  Flu  dan  Batuk.  The launching  of  Bodrex  Flu  dan  Batuk  will  affect  Bodrex’s  brand  image.  The objective of this research is to examine the influence of Bodrex Flu dan Batuk on Bodrex’s brand  image.  This  research  was  conducted  in  Yogyakarta  using purposive  sampling  method  on  respondents  that  have  been  using  Bodrex  for  6 months.  Data  were  collected  by  using  questionnaire  with  Likert  scale  that measured  initial  brand  image,  category  fit,  image  fit,  consumers’  attitude towards  brand  extension,  innovativeness,  and  final  brand  image.  Structural Equation Modeling  (SEM) application was  used  to analyse data.  Research result showed that brand extension has its effect on Bodrex’s brand image, in which its final  brand  image  was  affected  significantly  by  consumers’  attitude  towards brand  extension  (t-value  =  4.88)  and  initial  brand  image  (t-value  =  15.14). However, initial brand image (standardized solution = 0,88) has a larger role in final  brand  image  formation  than  consumers’  attitude  towards  brand  extension (standardized  solution  =  0.15).  Consumers’  attitude  towards  Bodrex’s  brand extension  affected  significantly  by  image  fit  (t-value  =  5.29),  category  fit  (tvalue = 1.99) and insignificantly by initial brand image (t-value = 0.49). The   result    also    showed   that  innovativeness  significantly  (t-value  =  -2.79) moderates  category  fit  relation  with  consumers  attitude  towards  brand extension.Key words: brand extension, brand image, Bodrex, innovativeness